The problem of poor student education: Capital limitation & decision making in higher education - Rika Kartika (Universitas Negeri Yogyakarta, 2020)
This study aims to analyze how poor students learning problems are within the limitations of capital. And then, to explore how the decision making of poor students to continue higher education. The study was conducted at a private high school, East Jakarta, using a qualitative approach and case study method. Data collection techniques with interviews, observation, and study documents. The problem of low student education will continue as long as social class differences exist. The contrast of social class plays a role in almost all aspects of education, like learning achievement and educational choices differences. This study shows poor students' inability to get learning achievement because limited economic capital makes the other money little. Poor students who have low achievement don't pursue higher education. They chose to work early, appearing almost as an